COACHING CLINIC STRETCHING AND COLLINGDOWN AT MAHAMERU BASKETBALL CLUB PEKANBARU - Oki Candra; Ahmad Rahmadani; Alvi Renanda; Fitra Ramadhan (Bajang Institute, 2022)
Basketball is a high-intensity sport with a time of 4x10 minutes. For that basketball is a sport that requires extraordinary physical conditions. Before playing basketball we are required to warm up first, with a good warm-up it will maximize the muscles to avoid sports injuries. The problem in the field is that there are still many athletes who do not understand the concept of good and correct stretching and collingdown in doing it. There are still many athletes who warm up and cool down carelessly and haphazardly, not paying attention to the occurrence of injuries immediately in the game, then there are still athletes who do not do stretching and colling down before exercising specifically in basketball and there are still athletes who do not attach importance to the occurrence of injuries and how the psychological impact on life daily. The planned activities to be held are in the form of a coaching clinic and the following sequence, 1) theoretically explaining the importance of stretching and collingdown for our bodies before and after exercise, 2) the impact of not doing stretching and collingdown, 3) psychological impact if an injury occurs on the body sports, 4) invite athletes together to practice directly how to stretch and colling down properly and correctly. The results of the coaching clinic activities about warming up and cooling down for basketball athletes from Mahameru showed an increase in all athletes before and after doing stretching and collingdowns properly and correctly. This proves that the coaching clinic that we hold for basketball athletes from Mahameru Pekanbaru has succeeded in achieving the expected goals of conducting workshops in theory and practice and everything is going well.